2007
DOI: 10.1016/j.biopsych.2006.07.028
|View full text |Cite
|
Sign up to set email alerts
|

White-Matter Integrity Predicts Stroop Performance in Patients with Geriatric Depression

Abstract: Background-This study tested the hypothesis that microstructural white matter abnormalities in frontostriatal-limbic tracts are associated with poor response inhibition on the Stroop task in depressed elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
103
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(115 citation statements)
references
References 51 publications
(43 reference statements)
5
103
1
3
Order By: Relevance
“…44,[53][54][55][56] Diffusion tensor imaging studies have also shown microstructural white matter abnormalities in fronto-striatal-limbic networks, including the lateral to anterior and posterior cingulate cortices and the prefrontal, insular and parahippocampal regions, are associated with executive dysfunction in patients with LLD. 46,57 A grey matter volume increase was observed in the right lingual gyrus both in the pooled meta-analysis and the subgroup meta-analysis. This brain region is not typically implicated in mood disorders.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…44,[53][54][55][56] Diffusion tensor imaging studies have also shown microstructural white matter abnormalities in fronto-striatal-limbic networks, including the lateral to anterior and posterior cingulate cortices and the prefrontal, insular and parahippocampal regions, are associated with executive dysfunction in patients with LLD. 46,57 A grey matter volume increase was observed in the right lingual gyrus both in the pooled meta-analysis and the subgroup meta-analysis. This brain region is not typically implicated in mood disorders.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings are in line with those of a postmortem study of patients with major depressive disorder that reported decreases in the density or number of glia and the density and size of neurons in the ACC 43 in patients with LLD. Functional neuroimaging studies have also reported decreased spontaneous neural activity in the right ACC and the bilateral medial prefrontal gyrus [44][45][46] in patients with LLD relative to controls. It is striking that the subcallosal gyrus, which was identified in this meta-analysis, is an important target for deep brain stimulation treatment for treatment-resistant depression, with good long-term safety and antidepressant efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…16 Region of interest (ROI)-based DTI studies in patients with late-life depression have consistently reported reduced fractional anisotropy values in prefrontal brain regions. [17][18][19][20][21][22] Reduced fractional anisotropy in the cingulate cortex has also been detected. 19,23,24 In addition, Yang and colleagues 22 and Murphy and colleagues 19 reported a reduction in fractional anisotropy values in the parahippocampal gyrus.…”
Section: Introductionmentioning
confidence: 90%
“…[17][18][19][20][21][22] Reduced fractional anisotropy in the cingulate cortex has also been detected. 19,23,24 In addition, Yang and colleagues 22 and Murphy and colleagues 19 reported a reduction in fractional anisotropy values in the parahippocampal gyrus. On the other hand, Lu and colleagues 25 detected an increase in fractional anisotropy values in areas of the brain associated with mood regulation, such as the right superior frontal gyrus to right pallidum and left superior parietal gyrus to right super ior occipital gyrus, by performing tractography analysis in patients with MDD.…”
Section: Introductionmentioning
confidence: 90%
“…Behavioral studies showing abnormally high interference effects in Stroop paradigms by patients with HIV-alcoholism comorbidity (Schulte et al 2005) or late-life depression (Murphy et al 2006) provide inferential evidence for degraded integrity of the intrahemispheric frontoparietal attention network. Our current findings extend this functional network to include interhemispheric effects of HIV-alcoholism comorbidity on Stroop interference effects.…”
Section: Discussionmentioning
confidence: 99%